Determination of Natural Gas Consumption and Carbon Emission in Natural Gas Supplying Countries in Asia Pacific - Aimon, Hasdi; Kurniadi, Anggi Putri; Triani, Mike (International Journal of Energy Economics and Policy, 2022)
This study investigates determination of natural gas consumption and carbon emission in the middle income group of natural gas supplying countries in Asia Pacific, including China, Indonesia, Malaysia, Myanmar and Vietnam during the period 2000-2021 by applying the simultaneous equation analysis. The results of this study are that carbon emission increase due to the real exchange rate, population and natural gas production, but carbon emission will reduce natural gas consumption. Furthermore, natural gas consumption increases due to natural gas production, GDP per capita and energy intensity. This study recommends the government to develop clean and efficient alternative energy to reduce carbon emission in response to natural gas demand for domestic and foreign market needs.